2002
DOI: 10.1002/hup.469
|View full text |Cite
|
Sign up to set email alerts
|

Possible predictors of response to fluvoxamine for depression

Abstract: Age, the frequency of episodes and the daily dose of fluvoxamine may be considered as predictors of the response to fluvoxamine treatment for depression. This result should be examined in future prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
4
0
3
Order By: Relevance
“…For fluvoxamine, age under 49 years and a first episode were important factors (Morishita and Arita, 2003a). For paroxetine, a first episode was important (Morishita and Arita, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For fluvoxamine, age under 49 years and a first episode were important factors (Morishita and Arita, 2003a). For paroxetine, a first episode was important (Morishita and Arita, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Yaşın AD tedaviye cevap üzerine olan etkisi bu amaçla yapılmış çalışmalarda fazlasıyla araştırılmış bir konudur. Daha genç olan hastaların, AD tedaviye daha olumlu yanıt verdiğini ifade eden çalışmalar bulunmaktadır (32,33,34,35). Ancak buna karşın Joyce ve ark.…”
Section: Discussionunclassified
“…Kısa hastalık süresinin AD tedavi ile düzelme ihtimalini arttırdığı (41,42,43) uzun hastalık süresinin ise azalttığı (33,37,44) vurgulanmaktadır. Aynı zamanda hastalık süresiyle dolaylı olarak bağlantılı olan daha önce geçirilmiş atak sayısının fazla olmasının, hastanın AD tedaviye cevap verme ihtimalini düşürdüğü iddia edilmektedir (35,45,46). Yani akut, dolayısıyla hastalık süresi kısa olan ve tekrarlayıcı olmayan depresyonun AD tedaviye daha iyi cevap verdiği belirtilmektedir (34,36,43,47).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In a comparative study of fluvoxamine versus imipramine for major depressive patients, no difference between these two antidepressants was indicated in 12 trials, while fluvoxamine was found to be superior in two trials 2 . Morishita and Arita reported that age, the frequency of episodes, and the daily dose of fluvoxamine might be considered as predictors of the response to fluvoxamine treatment for depression 3 . In contrast, it has been reported that the responders to fluvoxamine or paroxetine had significantly higher plasma‐free 3‐methoxy‐4‐hydroxyphenylglycol (pMHPG) levels before administration of fluvoxamine or paroxetine than did the non‐responders 4,5 .…”
mentioning
confidence: 99%